(untitled) (Salud, Arte y Cuidado, 2024)
Neck pain is a frequent cause of medical consultation, both in primary care and in specialized and emergency care. It is estimated that more than half of the population suffers from neck pain at some point in their lives, which leads to high levels of absenteeism, compensation, early retirement and even disability in the western world. The objective of this study being to describe the clinical-epidemiological characteristics of neck pain in patients who attend the Regional Center for Physical Medicine and Rehabilitation Dr. "Regulo Carpio López" of the Central University Hospital Dr. "Antonio María Pineda", Barquisimeto, Lara state. A descriptive cross-sectional study was carried out taking as a population the patients who attended the general consultation in the period November 2019 to March 2020, who had been diagnosed with said pathology. The data were collected in a data collection form with the variables age, sex, occupation, etiology of neck pain, time of evolution, intensity of pain, type of pain and characteristics on physical examination; the data obtained were processed using the SPSS version 18 program according to the study objectives. The results of this research showed that the disease is more common in women with 89.6%, aged from 28 to 37 years, 45.8% of these patients were professionals, being its cause 100% mechanical, in relation to the time of evolution, 50% were chronic neck pain, type of oppressive pain with 66.7%, EVA scale presenting moderate pain with 56.3%, radiating to the upper limb with 54.2%. The information provided will make it possible to have up-to-date statistical data on neck pain in said service, as well as to carry out an early and adequate diagnosis, which will increase the chances of indicating a timely and effective treatment for the disease, in order to reduce morbidity